PENGARUH MEDIA KARTU BERGAMBAR TERHADAP KEMAMPUAN MENGENAL BILANGAN PADA ANAK USIA 4-5 TAHUN DI PAUD RAUDHATUL JANNAH PEKANBARU - Rokiah Rokiah; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine how much influence the use of Media Picture Card Numbers to Know Your Ability in Children Aged 4-5 Years in early childhood Jannah Raudhatul Pekanbaru. The population and sample of this research is children aged 4-5 years amounted to 15 children. Data collection techniques were used that observation. The data analysis technique used in this study is a t-test. The results were obtained t = -6225 means greater than ttable the significant level of 5% and at significant level of 1% (-2.14 <-6225> -2.98). Thus, it means Ho is rejected. Thus there is significant influence between Media Picture Card Numbers to Know Your Ability in Children Aged 4-5 Years in early childhood Jannah Raudhatul Pekanbaru.Keywords: ability to recognize numbers, media picture cards